2006
DOI: 10.1007/s00380-005-0870-4
|View full text |Cite
|
Sign up to set email alerts
|

Single high-dose bolus tirofiban with high-loading-dose clopidogrel in primary coronary angioplasty

Abstract: Glycoprotein IIb/IIIa inhibitor therapy during primary percutaneous coronary intervention (PCI) decreases the incidence of major adverse cardiac events. These effects directly result from the level of platelet inhibition. It was shown that standard dosing of tirofiban is insufficient for optimal platelet inhibition. We sought to determine the efficacy and safety of single high-dose bolus (HDB) tirofiban with high-dose clopidogrel loading in primary PCI in acute ST elevation myocardial infarction. A total of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…27 Furthermore, a significant association of the high-dose bolus of tirofiban and a higher rate of preprocedural TIMI-3 blood flow was observed. 28,29 Our register included STEMI patients who presented within 12 h from the onset of symptoms. The mean time from symptoms to first medical contact in our cohort was 2.5 h (range 1.5-4.0 h), and the mean time from first medical contact to balloon was 89-90 min (range 40-148 min).…”
Section: Discussionmentioning
confidence: 99%
“…27 Furthermore, a significant association of the high-dose bolus of tirofiban and a higher rate of preprocedural TIMI-3 blood flow was observed. 28,29 Our register included STEMI patients who presented within 12 h from the onset of symptoms. The mean time from symptoms to first medical contact in our cohort was 2.5 h (range 1.5-4.0 h), and the mean time from first medical contact to balloon was 89-90 min (range 40-148 min).…”
Section: Discussionmentioning
confidence: 99%
“…Severe focal vascular narrowing was detected in the M1 mid-portion in all patients. Intraarterially infused tirofiban doses ranged from 0.5 to 1.5 mg, which corresponded to 33 to 100% of the recommended IV high loading dose in percutaneous coronary intervention (25μg/kg) 7 . Improvement of the distal blood flow was rapidly achieved in all patients after IA administration of tirofiban (TICI grade 3 in all patients).…”
Section: Angiography Outcomesmentioning
confidence: 99%
“…Furthermore, double doses or high bolus doses of tirofiban given before PCI did not translate into better clinical outcomes. 6,7 With the combined use of stents, ADP antagonists, thienopyridines, aspirin, fibrinolytic agents, and now GP IIb/IIIa antagonists, patients with STEMI can benefit from both facilitated and mechanical reperfusion. GP IIb/IIIa inhibitors are but one in the armamentarium that deserves further investigation.…”
Section: Dosementioning
confidence: 99%
“…Numerous trials have evaluated the effect of GP IIb/IIIa inhibitors (tirofiban) on coronary patency, myocardial perfusion, and clinical outcomes in patients with STEMI but yielded conflicting results. [1][2][3][4][5][6][7][8] Favorable trends for clinical outcomes in both short-and long-term follow-up, when treatment is started early before the patient enters the catheterization laboratory, were Studies have shown conflicting results for glycoprotein IIb/IIIa inhibitor (tirofiban) use in ST-segment elevation myocardial infarction (STEMI). The authors aimed to determine if an upstream conventional dose of tirofiban in addition to a standard treatment regimen improved coronary patency and clinical outcomes in patients with STEMI.…”
Section: Introductionmentioning
confidence: 98%